PENGARUH LAMA USAHA, PEMAHAMAN AKUNTANSI DAN DIGITALISASI UMKM TERHADAP KUALITAS LAPORAN KEUANGAN UMKM DI KOTA BATAM - Junianti Junianti; Risca Azmiana (LPPM Universitas Putera Batam, 2026)
This study aims to comprehensively analyzed the effects of business tenure, accounting understanding, and MSMEs digitalization on the quality of MSMEs financial reports in Batam City. The researches method is quantitative, emphasizing primary data collection through a carefully designed questionnaire. The data collection process utilized the Google Forms platform and a direct approach to respondents. Data analys in this study involves descriptive analysis methods as well as in-depth quantitative analysis, including data quality test, classical assumption test, multiple linear regression analys, and hypothesis test. Researches results show that business tenure has a positive and significant impact on the quality of MSMEs financial reports. Furthermore, accounting understanding had a positive and significant impact on the quality of MSMEs financial reports. Last, MSMEs digitalization significantly impacts the quality of financial reports. The use of information technology in financial recording and management activities helps improve the efficiency, speed, and accuracy of the reporting process. The combination of business tenure, accounting understanding, and MSMEs digitalization will result in more effective quality MSMEs financial reports. The interaction of these three factors results in more orderly, relevant, and reliable financial reports.